The Semiotic Analysis of The Jember Fashion Carnaval 2023’s Posters - Leny Fransista Agustin (Fakultas Ilmu Budaya, 2024)
This study aims to reveal the meaning constructed through the semiotic signs in the poster of Jember Fashion Carnaval. The study also aims to reveal the ideological interest constructed through the arrangement of defiles in the eleven posters of Jember Fashion Carnaval. The study belongs to a qualitative study. The data of this study were collected from the official website and official Instagram account of Jember Fashion Carnaval. The theory used in this study is the theory of semiotics by Roland Barthes (1991). The analysis revealed that the semiotic signs in the posters of Jember Fashion Carnival created a myth that the new capital of Indonesia in Kalimantan “Nusantara” would bring prosperity and bright future for the republic of Indonesia . The analysis reveals how a certain political ideology is disguised and transformed into nature through the semiotic signs in the posters of Jember Fashion Carnaval 2023 “Timelapse”.
Reupload file repository 11 februari 2026 maya/mita
Keywords: Jember Fashion Carnaval; Myth; Semiotics